1991
DOI: 10.1159/000235385
|View full text |Cite
|
Sign up to set email alerts
|

Late Phase Increase of Thrombin-Like Proteinase, Protein, Leukocytes in Bronchoalveolar Lavage (BAL) Fluid and Chemiluminescence of BAL after Ovalbumin Aerosol Inhalation by Actively Immunized Rats

Abstract: A thrombin-like proteinase (THROLP) was detected colorimetrically as the main proteolytic activity (PROA) in bronchoalveolar lavage fluid (BALF) 4 and 24 h after ovalbumin aerosol (OVA) challenge of actively immunized rats. Other proinflammatory parameters increased also significantly in BALF, like chemiluminescence of leukocytes (1 h), protein and cell number (24 h after challenge). In parallel, increased bronchoconstrictions against 5-HT aerosols are detected 24 h post OVA challenge. THROLP is an indicator f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thrombin‐like proteinases have been found in bronchoalveolar lavage fluids obtained from active immunized experimental animals ( Linssen et al ., 1991 ). The role of coagulation cascade activation and fibrin deposition during lung inflammation has been investigated; it has been shown that asthmatic subjects present alterations in coagulation parameters and an increase of platelet reactivity ( Idell et al ., 1989 ; Gresele et al ., 1993 ; Fuchs‐Buder et al ., 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin‐like proteinases have been found in bronchoalveolar lavage fluids obtained from active immunized experimental animals ( Linssen et al ., 1991 ). The role of coagulation cascade activation and fibrin deposition during lung inflammation has been investigated; it has been shown that asthmatic subjects present alterations in coagulation parameters and an increase of platelet reactivity ( Idell et al ., 1989 ; Gresele et al ., 1993 ; Fuchs‐Buder et al ., 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of enzymes might be increased in BALF following allergen challenge; Ihesc include mast cell tryptase [27]. plasma kallikrein [28], tissue kallikrein [I] and thrombin and piasminogen [29]. Of these enzymes, mast cell tryptase and the kallikreins at least are capable of generating kinins from kininogens [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…By multiplication with factor 2.3, the values for PROA in PLF were transformed into their corresponding activities at 37°C. This allows a better comparison to data obtained at 37°C from analysis of rat bron choalveolar lavage fluid, plasma and serum in another study [8]. The final dilution of PLF in the samples corresponded to 1:12.…”
mentioning
confidence: 99%
“…Previously, we found that PROA, which preferentially splits the thrombin-selective chromogenic substrate CHr® TH, was released in vitro in parallel with histamine (H) from washed leukocytes of atopies after allergen challenge [5]. A similar thrombin-like proteinase (THROLP) was detected in the supernatant of washed peritoneal mast cells from actively sensitized rats, fol lowing antigen stimulation, together with chymotrypsin-like proteinase (CHYLP) and H [6,7], THROLP was also the prominent PROA in bronchoalveolar la vage fluid which was collected from immunized rats during the protracted inflammation of the airways 4-24 h after inhalation of antigen aerosol [8]. There fore, THROLP appears to be a suitable parameter for allergic and inflammatory reactions.…”
mentioning
confidence: 99%